Neuromuscular Exercises Improve Shoulder Function More Than Standard Care Exercises in Patients With a Traumatic Anterior Shoulder Dislocation: A Randomized Controlled Trial. Issue 1 (30th January 2020) - Eshoj, Henrik Rode; Rasmussen, Sten; Frich, Lars Henrik; Hvass, Inge; Christensen, Robin; Boyle, Eleanor; Jensen, Steen Lund; Søndergaard, Jens; Søgaard, Karen; Juul-Kristensen, Birgit
Background: There is an important gap in knowledge about the effectiveness of nonoperative treatment (exercise) for patients with traumatic primary and recurrent anterior shoulder dislocations (ASDs). Purpose/Hypothesis: The purpose of this study was to assess the efficacy and safety of physical therapist–supervised, shoulder instability neuromuscular exercise (SINEX) versus self-managed, home-based, standard care shoulder exercise (HOMEX) in patients with traumatic ASDs. The hypothesis was that SINEX would have a larger effect and fewer adverse events compared with HOMEX. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: A total of 56 participants with radiographically verified, trauma-initiated primary or recurrent ASDs and self-reported decreased shoulder function were randomized to 12 weeks of either SINEX or HOMEX. The SINEX program consisted of 7 exercises, individually progressing from basic (2 × 20 repetitions each day) to elite (2 × 10 repetitions, 3 times weekly). The HOMEX program included 5 shoulder exercises performed 3 times weekly (2 × 10 repetitions). The primary outcome was the Western Ontario Shoulder Instability Index (WOSI) score, ranging from 0 (best possible) to 2100. The between-group minimal clinically important difference at 12 weeks was 250 points. Secondary outcomes included WOSI subdomain scores, patient-reported ratings of kinesiophobia and pain, objective shoulder function, patient satisfaction, and number of adverse events. Results: The between-group mean difference in the WOSI total score at 12 weeks significantly favored SINEX over HOMEX (–228.1 [95% CI, –430.5 to –25.6]). SINEX was furthermore superior to HOMEX in most of the secondary outcomes (3/4 subdomains of the WOSI and pain level during the past 7 days as well as clinical signs of anterior shoulder instability). Also, although not statistically significant, less than half the proportion of the SINEX patients compared with the HOMEX patients (3/27 [11%] vs 6/24 [25%], respectively; P = .204) underwent or were referred for shoulder stabilizing surgery. Satisfaction with both exercise programs was high, and no serious adverse events were reported. Conclusion: Neuromuscular shoulder exercise (SINEX) was superior to standard care exercise (HOMEX) in patients with traumatic ASDs. Further long-term follow-ups on treatment effects are needed. Registration: NCT02371928 (ClinicalTrials.gov identifier).